Legal aspects of biobanking HBS for scientific purposes in Poland (Studia Prawnicze / The Legal Studies, 2019)
Legal issues related to the biobanking of human biological samples are one of the extremely important areas of European law. Biobanks created in Poland as well as the Polish Biobank Network created under the auspices of the Ministry of Science and Higher Education have become a catalyst for the search for solutions and the basis of rights for the functioning of biobanks in Poland as well as the protection of donor rights. Undoubtedly, the lack of legal regulation of biobanks and biomedical research on human biological samples could become a significant problem limiting the development of biobanking and conducting scientific research in Poland. The research attempts to show how representatives of the doctrine of law, bioethics and sociologists have interpreted the principles and standards of biobank operation in Poland from basic human rights, constitutional norms and personal rights.